Pengaruh Konten Review dan Electronic Word Of Mouth Terhadap Minat Beli Mobil Listrik (Studi Kuantitatif Pada Channel Youtube Fitra Eri, Ridwan Hanif, dan Oto Driver) - Lis Aprilia; Yolanda Presiana Desi; Sigit Purnomo (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
YouTube is a social media platform with a high level of success in digital marketing. Some examples of digital marketing strategies on YouTube include review content and electronic-word of mouth, which are available in the comment section. The success of digital marketing on YouTube is also evident with the increasing popularity of electric cars review content, resulting in a drastic increase in electric cars sales since 2020. An electric car is a car powered by stored electrical energy in a battery or other sources. This study aims to examine the influence of review content and electronic-word of mouth on YouTube on the purchase intention of electric cars. The method used is a quantitative method with 100 respondents who have watched the review videos of Wulling Air Ev and Hyundai Ioniq electric cars on YouTube channels of Fitra Eri, Ridwan Hanif, and Oto Driver. The selected samples were chosen using non probability sampling techniques with purposive sampling. The data were collected through Google Form. The data were tested using SPSS 17 software through several tests such as instrument testing (validity and reliability), classical assumption testing (normality, linearity, heteroscedasticity, autocorrelation), hypothesis testing (multiple linear regression, R-squared, t-test, F-test). The research results show that: 1). The variable of electric cars review content has a 16% influence on purchase intention. 2). The eWOM variable has a 70% influence on purchase intention. 3). The combined influence of review content and eWOM on purchase intention is 32.5%.